Efficacy and Safety of Travoprost Intraocular Implants in Open-Angle Glaucoma and Ocular Hypertension: A Systematic Review and Meta-Analysis - Jovita Jutamulia; Agnestya Christine Zely Raule (HM Publisher, 2026)
Background: Open-angle glaucoma (OAG) and ocular hypertension (OHT) are leading causes of irreversible visual impairment and require lifelong reduction of intraocular pressure (IOP). Topical prostaglandin analogues are the standard first-line therapy, yet their effectiveness is constrained by poor adherence. The travoprost 75 µg intracameral implant has emerged as a sustained-release alternative designed to bypass these adherence barriers. The present systematic review and meta-analysis quantitatively synthesised the efficacy and safety of this device in adults with OAG or OHT. Methods: PubMed was searched in accordance with the PRISMA 2020 statement. Original research articles evaluating the travoprost 75 µg intracameral implant in adults with OAG or OHT were eligible. Two reviewers screened, extracted data, and independently appraised risk of bias using Cochrane RoB 2.0 (RCTs) or the Newcastle–Ottawa Scale (non-randomised). Standardised mean changes in IOP were synthesised as Hedges' g under a DerSimonian–Laird random-effects model with Knapp–Hartung adjustment. Pre-specified sensitivity, leave-one-out, alternative-pool, and design sub-group analyses were performed. The funnel plot was inspected; Egger's test was deferred because k < 10. Results: Of 30 PubMed records, 10 original research studies were eligible and 6 contributed to the primary quantitative synthesis (2,152 total enrolled participants; 1,525 implant-arm participants pooled in the within-group synthesis). The pooled within-group Hedges' g for IOP reduction was 4.35 (95% CI 3.14 to 5.56; p = 0.0002). Heterogeneity was very high (I² = 96.1%, τ² = 1.121, Q = 53.64, p < 0.0001). The 95% prediction interval, derived from the same model, spanned approximately 1.13 to 7.56. The randomised-controlled-trial-only pool (k = 4) yielded a more conservative pooled estimate of g = 3.76 (95% CI 2.94 to 4.58; I² = 88.6%). Leave-one-out analyses confirmed robustness (g range 3.98–4.56). Serious ocular adverse events were rare (one endophthalmitis in the slow-eluting arm of the GC-010 phase 3 trial, with no further cases in the remaining cohorts); transient ocular hyperemia, iritis, and elevated IOP were the most common, broadly consistent with the topical-travoprost class profile. Conclusion: The travoprost 75 µg intracameral implant produced a large and consistent reduction in IOP across designs and follow-up windows, with a safety profile non-inferior to topical timolol 0.5%. The substantial heterogeneity, near-uniform sponsor footprint, and limited head-to-head comparisons against topical prostaglandin monotherapy temper the certainty of the evidence and warrant pragmatic, independent, multi-ethnic trials. Within these limits, the implant is a clinically meaningful addition to interventional glaucoma therapy, particularly for patients in whom topical adherence is the dominant driver of disease progression.